A survey of secondary school libraries in Manila - Sunio, Isabel S. 1909- (1952)
A survey of secondary school libraries in Manila was conducted in this study. It is the purpose of the survey to determine the strengths and weaknesses of high school library programs in Manila, to find ways in which these programs might be improved, and to suggest steps necessary for their improvement and the types of planning programs which must be formulated to effect the improvements. To carry out this purpose, four steps in the evaluative process have been taken: 1) The facilities and services existing in the secondary school libraries in Manila were surveyed. 2) These facilities and services were evaluated. 3) Other school library facilities and services which the school libraries do not have now, were considered on the basis of their potential contribution. 4) Recommendations for the formulation of a school library program was made.